CONTEMPORARY PERCEPTIONS OF GENDER DUE TO ONLINE GENDER-BASED VIOLENCE (OGBV) IN THE DIGITAL SOCIETY - Amaliya, Rizki; Wilodati; Komariah, Siti (Universitas Negeri Medan, 2024)
The increase in Online Gender-Based Violence (OGBV) has become a pressing issue, with cases rising annually. This trend has sparked widespread public discussions, particularly about contemporary gender perceptions in the digital realm. This study investigates these perceptions using social media platform Instagram, Twitter (X), and TikTok as case studies. Using a qualitative approach with Norman Fairclough's Critical Discourse Analysis (CDA), the research explores the text, discourse practices, and sociocultural dynamics in the responses to OGBV. Data was collected from comments on three speciMic OGBV cases, receiving between 100 and 1,000 responses across the platforms. The Mindings reveal that social media serves a dual purpose: it acts as a platform for solidarity and advocacy, enabling digital communities to support victims and raise awareness about women's rights and empowerment. However, it also perpetuates victim-blaming and reinforces traditional gender stereotypes, thereby upholding patriarchal structures. This reMlects a contradictory role that social media plays in shaping public views on gender and violence. While digital spaces provide opportunities for empowerment and social change, they also mirror and amplify regressive societal attitudes, presenting challenges to efforts aimed at achieving gender equality. The study highlights the complex interplay between progressive and regressive attitudes in the digital community’s reactions to gender violence. It emphasizes the need to address the contradictory nature of social media's inMluence on public perceptions of OGBV. By offering critical insights into the sociocultural tensions at play, the research helps us understand the role of digital platforms in shaping gender discourse in the digital age.